Self-sustaining energy as an alternative to power outages in the Pueblo Unido sector in 2024 - Montero Reyes, Yilena; Villacis, Anthony; Garces, Yandri; Loachamin, Roberth (Multidisciplinar (Montevideo), 2025)
Introduction: power outages are a common problem in many parts of the world due to various reasons, it is important to consider self-sustaining energy as a viable alternative.Objective: to determine the knowledge in the Pueblo Unido sector about self-sustaining energy as an alternative to power outages.Method: an observational, descriptive, and cross-sectional study was conducted to assess knowledge related to self-sustaining energy as an alternative to power outages in the Pueblo Unido sector in 2024.Results: 52.1 % are female, 43.8 % have power outages every month, 60.4 % usually have power outages for one hour, 52.1 % have problems with delays in household and work activities during the year, 54.2 % have ever considered installing self-sustaining energy systems, 87.5 % believe that the implementation of self-sustaining energy could reduce the frequency of power outages.Conclusions: the potential of self-sustaining energy systems based on motor and bicycle generators to address the challenges related to power outages is highlighted, while promoting sustainability, resilience, and community well-being